What happens when you trust your supervisor? Mediators of individual performance in trust relationships - Li, Ning (Institutional Knowledge at Singapore Management University, 2013)
To understand how trust in supervisor translates into individual job performance, we hypothesize that trust in supervisor facilitates positive psychological conditions of meaningfulness, safety, and availability, which in turn predict individual job performance. We assert that each of the three mediating paths in our model represents a distinct mechanism by which trust in supervisor contributes to individual job performance. We test our hypotheses with 206 supervisor–subordinate dyads and find that trust in supervisor contributes to job performance through psychological availability and psychological safety but not psychological meaningfulness. By examining three different psychological mechanisms within the same frame, we provide a test that compares and contrasts the uniqueness of the three pathways. Our findings suggest practical ways for managers to build trust with subordinates and guidance for the design of productive work conditions.